3 - Using ICTs to Enhance Healthcare in Zambia - Kutoma Jacqueline Wakunuma, (Africa Media Review, 2008)
This paper examines an electronic record system in Zambia, where Information and Communication Technologies (ICTs) have been adopted and are being used innovatively in one area of the health sector – perinatal care. The paper explores how the system known as the Zambia Electronic Perinatal Record System (ZEPRS) is being used in Lusaka, the capital city of Zambia. Having carried out fieldwork in 2005 where interviews were conducted and observations made in relation to the system, the paper makes the case that such use of ICTs is contributing to human development and subsequently helping to meet some of the Millennium Development Goals (MDGs). This paper therefore makes the case that ZEPRS, one of a first of its kind in sub-Saharan Africa, is a good example of a programme that is being used to meet United Nations (UN) MDGs, of which enhancement of health is one of them.